Ethiopia : 2010 Article IV Consultation and First Review of the Arrangement under the Exogenous Shocks Facility; Staff Report; Staff Supplements; and Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2010)
The Ethiopian authorities have been generally responsive to the policy recommendations from the 2008 Article IV Consultation. To help rebuild international reserves and improve external competitiveness, the authorities made another exchange rate adjustment (a 5 percent devaluation) on January 31, 2010. The overall fiscal balance during July-December 2009 indicates stronger revenue collection than programmed. Ethiopia has been resilient to the ongoing global crisis because remittances have remained stable in 2009/10, FDI has risen 20 percent, and imports are lower.